Handbook of research methods in behavioural economics : an interdisciplinary approach - Altman, Morris (Edward Elgar Publishing, 2023)
"This comprehensive Handbook addresses a wide variety of methodological approaches adopted and developed by behavioural economists, exploring the implications of such innovations for analysis and policy. Presenting analytical narratives from renowned economists and economic psychologists, the Handbook applies a broad array of methodological perspectives to behavioural economics. These span from bounded rationality, asymmetric information, and heuristics and biases to fast and frugal heuristics, rational agents and smart decision-makers, and capabilities improvements and institutional design. Chapters further explore diverse areas such as public policy, micro and macroeconomics, labour economics, the firm, decision-making, preference formation, punishment, love, altruism, trust, the environment, money and finance, health, and sports. Providing a pluralistic approach to behavioural economics, the Handbook ultimately introduces readers to an array of possible methodologies that can be adopted to address topical economic issues, as well as facilitating an enriched and nuanced understanding of human behaviour in an economic context. Comparing and contrasting different methodologies within behavioural and neoclassical economics, this dynamic Handbook will be an invaluable resource for undergraduate and postgraduate students enrolled in economics, social psychology, and marketing courses. Policymakers will also benefit from its examination of the implications of behavioural economics for real-world decision making and policy"--